Nonlinear state estimation and control applied to a manipulator robotic including drive motor - Lima, Jeferson J. de; Tusset, Angelo Marcelo; Janzen, Frederic Conrad; Piccirillo, Vinícius; Nascimento, Claudinor Bitencourt; Balthazar, José Manoel [UNESP]; Brasil, Reyolando M L R F (My University, 2014)
A robotic control design considering all the inherent nonlinearities of the robot engine configuration is developed. The interactions between the robot and joint motor drive mechanism are considered. The proposed control combines two strategies, one feedforward control in order to maintain the system in the desired coordinate, and feedback control system to take the system into a desired coordinate. The feedback control is obtained using State Dependent Riccati Equation (SDRE). For link positioning two cases are considered. Case 1: For control positioning, it is only used motor voltage; Case 2: For control positioning, it is used both motor voltage and torque between the links. Simulation results, including parametric uncertainties in control shows the feasibility of the proposed control for the considered system.
Keywords: Feedforward and feedback controls; control the position